Pilotprojekt Gropiusstadt : Jahrbuch 2007. (Berlin : Kulturnetzwerk Neukölln Berlin, 2008)
Athanassiadis, Kiki ; Bechtold, Matias ; Beck, Tenna ; Behrendt, Angela ; Berthold, Matthias ; Borchers, Patrick ; Brand, Martin ; Forbes, Tegan ; Frey, Franziska ; Geppert, Stella ; Günther, Ingke ; Wagner, Jörg ; Haselbek, Lisa ; Horstundireneschmitt ; Jüngling, Steffi ; Knobloch, Andrea ; Kürtz, Andrea ; Lehner, Verónica ; Lösel, Eckbert ; Mayer, Matthias Aka Mo Magic ; Moore, Padraic ; Farrelly, Gary ; Nakamura, Sandra ; Olbrich, Jürgen O. ; Orlaineta, Edgar ; Paas, Jürgen ; Palmtag, Jürgen ; Pfelder & Zaugg, Simone ; Ruhland, Grit & Elffriede ; Samant, Sharmila ; Songster, Miriam ; Hoevel, Christiane ten ; Sprengel, Doris ; Tingley, Jane
zie kast losse tijdschriften
Duits
boek